The Impact of Collaborative Leadership on Urban Church influence in Africa. - Ang'ana, Gilbert A. (IOSR Journal of Humanities And Social Science, 2019)
Over the past few decades, urban cities of Africa have experienced a rise in social, economic, political challenges. Poverty, hunger, ill-health, terrorism, political unrest, and violence are some of the issues still rampant in many African cities even today. Collaborative leadership entails bringing urban churches and other pertinent stakeholders together in collectively addressing the issues facing urban cities of Africa. In this article, we conduct a qualitative systematic review of the existing literature on collaborative leadership and church influence in Africa to elaborate on a theological model on urban church influence. After reviewing several journals articles, books, and pertinent non-journaled cases of collaborative leadership in the context of the urban church in Africa, we identify critical collaborative leadership practices necessary for urban churches in Africa to have successful influence and be a pertinent player in defining and resolving Africa’s urban challenges. These practices include shared control and power, leadership development, and the discipleship experience. We also identify a series of collaborative leadership benefits that are crucial in urban churches in Africa. These benefits include a greater sense of diversity, solidarity, inspiration, and collective strengths. The article concludes with a discussion of the implications of adopting collaborative leadership principles for church leaders and practitioners in the context of urban church influence in Africa.
Keywords: collaborative leadership; urban church influence; theological model